Spatial–temporal QoS assessment of the EV charging network considering power outages - Tang, Difei; Liu, Xiaofeng; Zhao, Tianyang; Wang, Qi (Frontiers in Energy Research, 2023)
The rapid expansion of electric vehicle charging networks (EVCNs) makes them the critical infrastructures bridging power and traffic systems. The EVCN could be vulnerable during the power outages at fast charging stations (FCSs), which are induced by planned maintenance or emergency load shedding. This paper proposes an approach to assess the impact of power outages on the quality-of-service of EVCN. Markov decision process is utilized to model the spatial-temporal randomness of EV movement in a graph-based EVCN. EV drivers’ charging decision is estimated by a fuzzy logic inference system. The spatial-temporal EV charging load at FCSs are formulated by a queueing-based nonlinear optimization problem. Yen’s algorithm is adopted to simulate the EV redistribution phenomenon of searching adjacent healthy FCSs in response to the power outage. Quality-of-service (QoS) indices are derived to assess the potential congestions in the adjacent healthy FCSs. The case studies demonstrate that power outages may cause congestion at the peripheral FCSs, exacerbating the QoS of the EVCN. Partial charging may alleviate the QoS deterioration in the event of FCS outages.